Thermal functional traits of Antarctic mosses link species identity, nitrogen availability and ecosystem processes - Andrew Forrest Clements; Hannah M. Prather; Angelica Casanova-Katny; Todd N. Rosenstiel; Matthew W. Chmielewski; Becky A. Ball; Sarah M. Eppley (Polar Biology, 2026)

Monitoring of Colorectal Cancer Screening Adherence Among African American Patients of North Florida Community Health Centers - John S. Luque; Gebre-Egziabher Kiros; Askal A. Ali; Sabrina L. Dickey; Matthew Vargas; Deloria R. Jackson; Ryan Mohorne; Tanvee Doddi; Kristin Wallace; Clement K. Gwede (Journal of Cancer Education, 2026)
In the United States, colorectal cancer (CRC) mortality rates are higher in African Americans compared to non-Hispanic whites, partly due to advanced stage cancer diagnosis. Timely CRC screening helps to increase CRC early detection and survival in this population. The objective of this monitoring study was to survey African American patients of Community Health Centers (CHC) in north Florida and to monitor CRC screening adherence (either stool-based or colonoscopy) after they had completed a clinical trial testing a screening education intervention. Seventy-nine African American patients who were between the ages of 45 and 64 years old at the time of initial trial recruitment completed a 24-month follow-up survey, and 44% reported stool-based CRC screening in the last year. Results from the general estimating equations (GEE) model found there was a statistically significant difference in CRC screening adherence by study arm at 24 months where the intervention group was less likely to be up to date than the usual care control (OR = 0.60, 95% CI 0.43–0.83). Married or partnered participants (OR = 1.52, 95% CI 1.31–1.77) and employed participants (OR = 1.34, 95% CI 1.17–1.53) were more likely to be adherent to screening, but female participants were less likely to be adherent (OR = 0.76, 95% CI 0.70–0.82). Participants with higher mistrust in doctors were less likely to have completed screening (OR = 0.93, 95% CI 0.88–0.99). The findings suggest the importance of screening outreach to unmarried, unemployed, female African Americans. The results of this monitoring study indicate one-on-one cancer education with a community health advisor and education on the availability and functionality of electronic patient portals have potential for increasing adherence to recommended CRC screening. The study has implications for measuring CRC screening adherence in community settings.

Carry-over effects of decreased salinity on larval metamorphosis and the early juvenile in context with eReefs hydrodynamic models - Matthew Clements; Maria Byrne (Coral Reefs, 2026)
The environmental conditions experienced by marine invertebrate larvae can have carry-over effects on later life stage performance, affecting population dynamics. For crown-of-thorns sea stars (CoTS; Acanthaster spp.), the terrestrial runoff hypothesis (TRH) suggests that eutrophic runoff plumes boost larval phytoplankton food supply, increasing metamorphic success and seeding outbreaks. However, river plumes also decrease salinity which can be deleterious to sea star larvae. We investigated the impact of decreased salinity (17–30 PSU) across a range of exposure durations on survival, normal development, and the ability of settlement-ready brachiolaria larvae to produce a juvenile. Salinity performance curves identified salinity levels with deleterious effects and the tipping points for 50% normal development and survival. Decreased salinity and prolonged exposure reduced larval survival and morphology. To examine carry-over effects on metamorphosis and juvenile production, competent brachiolaria that had been exposed to decreased salinity were induced to settle. Juvenile production was highest in slightly reduced (30 PSU) and control (34 PSU) salinity treatments, with faster transition to the juvenile under extended 30 PSU exposures. However, by 5 days post-settlement juveniles produced by larvae from the 30 PSU treatment were smaller indicating the presence of negative carry-over effects that reduce juvenile quality. Larval salinity sensitivity and metamorphic success were evaluated against eReefs modelled low-salinity plumes affecting offshore reefs. Case studies from three runoff events indicate larvae may experience harmful conditions. Our results highlight the need to consider plume dynamics and COTS metamorphic transitions when assessing the TRH.

The fragility of the Uranian moons during the giant planet instability - Matthew S. Clement; Nathan A. Kaib; André Izidoro; Rogerio Deienno (Icarus, 2026)

Phytoremediation of an acid tar pit at Cinderhill, Derbyshire, UK: Lessons learned and future challenges - Matthew F. Johnson; Harvey Wood; Samantha Bryan; Sean Craig; Will Meredith; Colin Snape; Clement N. Uguna (Journal of Environmental Management, 2026)

Growth, density, and property crime: A longitudinal county-level study in the USA, 2001–2007 - Matthew Thomas Clement; Nathan W. Pino; Nathaniel Dede-Bamfo; Jack DeWaard (The Social Science Journal, 2026)

The cannabinoid receptor 2 is an in vivo receptor of bisphenol A during bone formation - Matthew J. Dubuisson; Carol K. Cox; Jasleen Kaur; McLean H. Williamson; Wilson K. Clements; Madelyn K. Logan; Jerry D. Monroe; Yann Gibert (Journal of Hazardous Materials, 2026)

Microplastics and anammox: Unravelling the hidden threats to nitrogen cycling and microbial resilience - Wajiha Sarfraz; Munawar Hussain; Clement Matthew Chan; Chengrong Chen; Noreen Khalid; Bahar S. Razavi; Mehran Rezaei Rashti (Journal of Hazardous Materials, 2026)

Unlocking opportunities for meaningful participation of land reform beneficiaries in the wildlife economy - Siviwe Shwababa; Matthew F. Child; Alta de Vos; Naledi Mneno; Hayley S. Clements (Land Use Policy, 2025)

Pharmacokinetics and Pharmacodynamics of Nomlabofusp in Non-clinical Studies of Friedreich’s Ataxia - Flavia De Toni; Vanessa Ragaglia; Devin Schecter; Angela S. Miller; Eric Gonzalez; Erik J. Wagner; Xin Xu; R. Mark Payne; Jean-Nicholas Mess; Matthew G. Baile; Adrienne Clements-Egan; Gopi Shankar (The AAPS Journal, 2025)
Nomlabofusp is a cell penetrant peptide-based recombinant fusion protein designed to enter cells and deliver human frataxin into the mitochondria of adults and children with Friedreich’s ataxia. In this article we present non-clinical studies evaluating the pharmacology of nomlabofusp, including in a murine striated muscle tissue frataxin knockout model of Friedreich’s ataxia. We demonstrate that subcutaneous administration of nomlabofusp distributes in a dose-dependent manner to several organs including the dorsal root ganglion, heart, and skeletal muscle, which are known to be predominantly affected in Friedreich’s ataxia, as well as to other tissues, including skin. Plasma nomlabofusp concentrations correlated with levels of human frataxin delivered by nomlabofusp into tissues, and the increases in frataxin were correlated amongst tissues, especially with skin. In the knockout mice, we show that the pharmacokinetics and processing of nomlabofusp were comparable with wild type animals and that treatment with nomlabofusp halts the progression of cardiac dysfunction and significantly increased survival. Together, the findings from these non-clinical studies demonstrate that nomlabofusp exposure increases human frataxin in Friedreich’s ataxia-relevant tissues and provide evidence of pharmacologic effects. Graphical Abstract

Immediate and short-term effects of pile-driving on Hector’s dolphin in Lyttelton Harbour, Aotearoa New Zealand - Deanna M. Clement; Heloise Pavanato; Crystal Lenky; Matthew K. Pine (Frontiers in Marine Science, 2025)
Ports in Aotearoa New Zealand have or are currently undergoing extensive infrastructure developments to accommodate the global trend in larger commercial vessels and cruise ships. With no national standards for underwater noise, Lyttelton Port Company is the first Aotearoa New Zealand port to undertake monitoring to assess pile-driving generated noise effects on local Hector’s dolphins, an endemic and nationally vulnerable species. The immediate and shorter-term responses of this species were monitored with autonomous underwater recorders and assessed to understand how dolphins reacted to pile-driving activities. General and site-specific model results indicated that as sound exposure levels from impact pile-driving increased, declines in dolphin detections varied spatially with immediate declines occurring at sites less than 1km for the source. Declines in detections were still apparent up to 2km, but more evident with greater noise exposure levels and in warmer water conditions. Once piling ceased for a day, Hector’s dolphins moved back into inner harbor waters within hours, and acoustic detections returned to within pre-piling levels gradually over a few days. While there is no evidence that dolphins abandoned the port region over the construction period, our findings established a longer-term decline in dolphin detections coinciding with the 2019 construction period that had not returned to pre-construction levels by May 2020. Despite evidence that mitigation measures were successful at protecting against auditory injury impacts, additional measures are warranted for future port infrastructure developments to avoid short and longer term impacts on Hector’s dolphin use of the harbor and while Aotearoa New Zealand develops or adopts national underwater noise guidelines.

The impact of functional additives on biodegradable plastic biodegradation in natural terrestrial and composting environments - Clement Matthew Chan; Serena Yim; Paul Lant; Steven Pratt; Bronwyn Laycock (Critical Reviews in Environmental Science and Technology, 2025)

Identifying gaps in the conservation of small wild cats of Southeast Asia - Luca Chiaverini; David W. Macdonald; Andrew J. Hearn; Żaneta Kaszta; Eric Ash; Özgün Emre Can; Phan Channa; Susan M. Cheyne; Gopalasamy Reuben Clements; Iding Achmad Haidir; Jan F. Kamler; Pyae Phyoe Kyaw; et al. (Biodiversity and Conservation, 2025)
Southeast Asia hosts more felid species than any other region and, although smaller (

Agronomic and environmental effects of forage-cutting schedule and nitrogen fertilization for bermudagrass (Cynodon dactylon, L.) - Clement D.D. Sohoulande; Liwang Ma; Zhiming Qi; Ariel Szogi; Kenneth Stone; Daren R. Harmel; Jerry H. Martin; Girma Birru; Matthew Sima (Agriculture, Ecosystems & Environment, 2025)

Lifetimes and mechanisms of biodegradation of polyhydroxyalkanoate (PHA) in estuarine and marine field environments - Tracey Read; Céline Chaléat; Bronwyn Laycock; Steven Pratt; Paul Lant; Clement Matthew Chan (Marine Pollution Bulletin, 2024)

The impact of simulated total surface current velocity observations on operational ocean forecasting and requirements for future satellite missions - Jennifer Waters; Matthew J. Martin; Isabelle Mirouze; Elisabeth Rémy; Robert R. King; Lucile Gaultier; Clement Ubelmann; Craig Donlon; Simon Van Gennip (Frontiers in Marine Science, 2024)
Operational forecasts rely on accurate and timely observations and it is important that the ocean forecasting community demonstrates the impact of those observations to the observing community and its funders while providing feedback on requirements for the design of the ocean observing system. One way in which impact of new observations can be assessed is through Observing System Simulation Experiments (OSSEs). Various satellite missions are being proposed to measure Total Surface Current Velocities (TSCV). This study uses OSSEs to assess the potential impact of assimilating TSCV observations. OSSEs have been performed using two global ocean forecasting systems; the Met Office’s (MetO) Forecasting Ocean Assimilation Model and the Mercator Ocean International (MOI) system. Developments to the individual systems, the design of the experiments and results have been described in two companion papers. This paper provides an intercomparison of the OSSEs results from the two systems. We show that global near surface velocity analysis root-mean-squared-errors (RMSE) are reduced by 20-30% and 10-15% in the MetO and MOI systems respectively, we also demonstrate that the percentage of particles forecast to be within 50 km of the true particle locations after drifting for 6 days has increased by 9%/7%. Furthermore, we show that the global subsurface velocities are improved down to 1500m in the MetO system and down to 400m in the MOI system. There are some regions where TSCV assimilation degrades the results, notably the middle of the gyres in the MetO system and at depth in the MOI system. Further tuning of the background and observation error covariances are required to improve performance in these regions. We also provide some recommendations on TSCV observation requirements for future satellite missions. We recommend that at least 80% of the ocean surface is observed in less than 4 to 5 days with a horizontal resolution of 20 to 50 km. Observations should be provided within one day of measurement time to allow real time assimilation and should have an accuracy of 10 cm/s in the along and across track direction and uncertainty estimates should be provided with each measurement.

The effect of additives on the biodegradation of polyhydroxyalkanoate (PHA) in marine field trials - Tracey Read; Clement Matthew Chan; Céline Chaléat; Bronwyn Laycock; Steven Pratt; Paul Lant (Science of The Total Environment, 2024)

More realistic planetesimal masses alter Kuiper belt formation models and add stochasticity - Nathan A. Kaib; Alex Parsells; Simon Grimm; Billy Quarles; Matthew S. Clement (Icarus, 2024)

CamTrapAsia : A dataset of tropical forest vertebrate communities from 239 camera trapping studies - Calebe P. Mendes; Wido R. Albert; Zachary Amir; Marc Ancrenaz; Eric Ash; Badrul Azhar; Henry Bernard; Jedediah Brodie; Tom Bruce; Elliot Carr; Gopalasamy Reuben Clements; Glyn Davies; et al. (Ecology, 2024)
Information on tropical Asian vertebrates has traditionally been sparse, particularly when it comes to cryptic species inhabiting the dense forests of the region. Vertebrate populations are declining globally due to land‐use change and hunting, the latter frequently referred as “defaunation.” This is especially true in tropical Asia where there is extensive land‐use change and high human densities. Robust monitoring requires that large volumes of vertebrate population data be made available for use by the scientific and applied communities. Camera traps have emerged as an effective, non‐invasive, widespread, and common approach to surveying vertebrates in their natural habitats. However, camera‐derived datasets remain scattered across a wide array of sources, including published scientific literature, gray literature, and unpublished works, making it challenging for researchers to harness the full potential of cameras for ecology, conservation, and management. In response, we collated and standardized observations from 239 camera trap studies conducted in tropical Asia. There were 278,260 independent records of 371 distinct species, comprising 232 mammals, 132 birds, and seven reptiles. The total trapping effort accumulated in this data paper consisted of 876,606 trap nights, distributed among Indonesia, Singapore, Malaysia, Bhutan, Thailand, Myanmar, Cambodia, Laos, Vietnam, Nepal, and far eastern India. The relatively standardized deployment methods in the region provide a consistent, reliable, and rich count data set relative to other large‐scale pressence‐only data sets, such as the Global Biodiversity Information Facility (GBIF) or citizen science repositories (e.g., iNaturalist), and is thus most similar to eBird. To facilitate the use of these data, we also provide mammalian species trait information and 13 environmental covariates calculated at three spatial scales around the camera survey centroids (within 10‐, 20‐, and 30‐km buffers). We will update the dataset to include broader coverage of temperate Asia and add newer surveys and covariates as they become available. This dataset unlocks immense opportunities for single‐species ecological or conservation studies as well as applied ecology, community ecology, and macroecology investigations. The data are fully available to the public for utilization and research. Please cite this data paper when utilizing the data.

Landfill intermediate cover soil microbiomes and their potential for mitigating greenhouse gas emissions revealed through metagenomics - Peyton H. Lienhart; Venus Rohra; Courtney Clement; Lucinda C. Toppen; Amy C. DeCola; Donna M. Rizzo; Matthew J. Scarborough (Science of The Total Environment, 2024)

Crash Chronicles: Relative contribution from comets and carbonaceous asteroids to Earth’s volatile budget in the context of an Early Instability - Sarah Joiret; Sean N. Raymond; Guillaume Avice; Matthew S. Clement (Icarus, 2024)

Inhibition of fatty acid binding protein-5 in the basolateral amygdala induces anxiolytic effects and accelerates fear memory extinction - Matthew J. Jones; Taygun C. Uzuneser; Timothy Clement; Hehe Wang; Iwao Ojima; Walter J. Rushlow; Steven R. Laviolette (Psychopharmacology, 2024)

Length-weight relationship for the dragonfish, Stichopus cf. monotuberculatus (Holothuroidea) - Benjamin C.T. Gray; Maria Byrne; Matthew Clements; Shawna A. Foo; Steven W. Purcell (Fisheries Research, 2023)

A race against the clock: Constraining the timing of cometary bombardment relative to Earth’s growth - Sarah Joiret; Sean N. Raymond; Guillaume Avice; Matthew S. Clement; Rogerio Deienno; David Nesvorný (Icarus, 2023)

Association of Preventive Care Attitudes and Beliefs with Colorectal Cancer Screening History among African American Patients of Community Health Centers - John S. Luque; Gebre-Egziabher Kiros; Matthew Vargas; Deloria R. Jackson; Olayemi O. Matthew; Tifini D. Austin; Rima Tawk; Askal A. Ali; Cynthia M. Harris; Kristin Wallace; Clement K. Gwede (Journal of Cancer Education, 2023)

Movement dynamics, sediment turnover and sheltering behaviours of the nocturnal coral reef sea cucumber, Stichopus cf. monotuberculatus - Benjamin C. T. Gray; Maria Byrne; Matthew Clements; Steven W. Purcell (Coral Reefs, 2023)
Animal movement and feeding studies shed light on ecological roles and can inform management strategies for fished species. However, the feeding and movement of nocturnal sea cucumbers have been rarely studied. We determined the movement dynamics, feeding ecology and sheltering behaviour of the nocturnal Stichopus cf. monotuberculatus (dragonfish) at One Tree Reef and Heron Island Reef on the southern Great Barrier Reef. The short-term movement of individual sea cucumbers were tracked, and sediment defecation rates were measured. Displacement rates averaged 3–33 cm h −1 across the four sites, with the sea cucumbers moving more slowly approaching sunrise and within patches of organically rich sediment. The movement paths were moderately tortuous, with larger sea cucumbers moving along straighter paths. Rates of sediment turnover averaged 7.8 g h −1 and were greatest for larger individuals. The faecal casts were organically richer and composed of finer grains than the ambient surface sediments, implying that S. cf. monotuberculatus avoids consuming coarse sediments and feeds on nutritionally rich particles. The sea cucumbers sheltered under hard reef substrata and moved non-directionally on the seascape, with a few individuals homing back to their original refuges. The affinity to reef substrata and short nightly net displacements of S. cf. monotuberculatus have implications for the spatial management of this and other similar species. Larger individuals occupied deeper refuges, implying that projected declines in substratum rugosity on coral reefs due to climate change could impact the size structure of sea cucumber populations, with implications for fisheries.

Juvenile waiting stage crown‐of‐thorns sea stars are resilient in heatwave conditions that bleach and kill corals - Maria Byrne; Dione J. Deaker; Mitchell Gibbs; Paulina Selvakumaraswamy; Matthew Clements (Global Change Biology, 2023)
The juveniles of predatory sea stars can remain in their recruitment–nursery habitat for some time before their ontogenetic shift to the adult habitat and diet. These small juveniles are vulnerable to a range of factors with their sensitivity amplified by climate change‐driven ocean warming. We investigate the thermal tolerance of the waiting stage herbivorous juveniles of the keystone coral predator, the crown‐of‐thorns sea star (COTS, Acanthaster sp.), in context with the degree heating weeks (DHW) model that predicts coral bleaching and mass mortality. In temperature treatments ranging from +1 to 3°C in prolonged heatwave acclimation conditions, the juveniles exhibited ~100% survival in DHW scenarios that trigger coral bleaching (4 DHW), resulting in mass mortality of corals (8 DHW) and extreme conditions well beyond those that kill corals (12 DHW). This indicates that herbivorous juvenile COTS are far more resistant to heatwave conditions than the coral prey of the adults. The juveniles exhibited higher activity (righting) and metabolic rate after weeks in increased temperature. In separate acute temperature experiments, the upper thermal limit of the juveniles was 34–36°C. In a warming world, juvenile COTS residing in their coral rubble nursery habitat will benefit from an increase in the extent of this habitat due to coral mortality. The juveniles have potential for long‐term persistence as herbivores as they wait for live coral to recover before becoming coral predators, thereby serving as a proximate source of COTS outbreaks on reefs already in a tenuous state due to climate change.

Synthesis and characterisation of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) multi-block copolymers comprising blocks of differing 3-hydroxyvalerate contents - Jingjing Mai; Christopher J. Garvey; Clement Matthew Chan; Steven Pratt; Bronwyn Laycock (Chemical Engineering Journal, 2023)

Discovery of the dendrophylliid scleractinian Heteropsammia cochlea (Spengler, 1781) in Halimeda bioherms of the Northern Great Barrier Reef - Stefano Borghi; Matthew Clements; Monique Webb; Helen Bostock; Jody M. Webster; Mardi McNeil; Luke Nothdurft; Maria Byrne (Marine Biodiversity, 2023)
Halimeda bioherms on the Northern Great Barrier Reef (GBR) extend for over 6000 km 2 . To explore the ecological and biogeographical importance of these bioherms was one of the aims of a recent voyage on the Research Vessel (RV) Investigator . Through the use of underwater images and habitat sampling, we found populations of Heteropsammia cochlea (Spengler, 1781) living in the bioherms. The scleractinian coral genus Heteropsammia (Dendrophylliidae) is a group of solitary, apozooxanthellate, single-polyp corals with a widespread distribution in tropical and sub-tropical regions. Populations of H. cochlea were observed with individuals dispersed on open-sand habitat and among patches of Halimeda at 30–40 m water depth in mean densities of 89 and 29 corals per m 2 , respectively. Fluorescence microscopy was used to assess the presence of zooxanthellae, indicating that they are actively photosynthesising at these depths. These are the first observations of H. cochlea in association with the Halimeda bioherms on the Northern GBR.

Mercury’s formation within the early instability scenario - Matthew S. Clement; John E. Chambers; Nathan A. Kaib; Sean N. Raymond; Alan P. Jackson (Icarus, 2023)

Comparisons of the core and mantle compositions of earth analogs from different terrestrial planet formation scenarios - Jesse T. Gu; Rebecca A. Fischer; Matthew C. Brennan; Matthew S. Clement; Seth A. Jacobson; Nathan A. Kaib; David P. O'Brien; Sean N. Raymond (Icarus, 2023)

Optimal risk-based allocation of disease surveillance effort for clustered disease outbreaks - Matthew J. Clement; Anne Justice-Allen; Jonathon D. Heale (Preventive Veterinary Medicine, 2023)

Rethinking the role of the giant planet instability in terrestrial planet formation models - Matthew S. Clement; Rogerio Deienno; André Izidoro (Icarus, 2023)

Determinants of sun bear Helarctos malayanus habitat use in Sabah, Malaysian Borneo and its predicted distribution under future forest degradation and loss - Roshan Guharajan; Jesse F. Abrams; Nicola K. Abram; Hong Ye Lim; Gopalasamy Reuben Clements; Nicolas J. Deere; Matthew J. Struebig; Benoit Goossens; Penny C. Gardner; Jedediah F. Brodie; Alys Granados; Shu Woan Teoh; et al. (Biodiversity and Conservation, 2023)

Engaging the Community on Colorectal Cancer Screening Education: Focus Group Discussions Among African Americans - John S. Luque; Matthew Vargas; Kristin Wallace; Olayemi O. Matthew; Rima Tawk; Askal A. Ali; Gebre-Egziabher Kiros; Cynthia M. Harris; Clement K. Gwede (Journal of Cancer Education, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

A bio‐available strontium isoscape for eastern Beringia: a tool for tracking landscape use of Pleistocene megafauna - Juliette Funck; Clement Bataille; Jeffrey Rasic; Matthew Wooller (Journal of Quaternary Science, 2021)
Numerous paleoecological questions concern the mobility of ancient fauna in eastern Beringia. Strontium (Sr) isotope ratio ( 87 Sr/ 86 Sr) analysis has emerged as a powerful tracer for determining the provenance of ancient biological materials. However, it is important to characterize 87 Sr/ 86 Sr variation across a landscape. We measured the 87 Sr/ 86 Sr composition of teeth from present‐day, herbivorous rodents ( n = 162) sampled from across eastern Beringia to estimate bio‐available 87 Sr/ 86 Sr values. We compiled these data with the very limited number of previously published 87 Sr/ 86 Sr values from the region. We then used this dataset and a machine learning, random‐forest regression to predict bio‐available 87 Sr/ 86 Sr variations across eastern Beringia. As a case study using our new 87 Sr/ 86 Sr map (isoscape), we measured the 87 Sr/ 86 Sr and oxygen stable isotope values (δ 18 O) of five radiocarbon‐dated steppe bison from eastern Beringia and compared these to our 87 Sr/ 86 Sr isoscape and a δ 18 O isoscape to estimate the probable landscape use of these ancient fauna. Our model and isoscape provide important foundations for a wide range of additional applications, including studies of the paleo‐mobility of other fauna, ancient people and present‐day fauna in eastern Beringia.

Modelling habitat use suggests static spatial exclusion zones are a non-optimal management tool for a highly mobile marine mammal - Sarah L. Dwyer; Matthew D. M. Pawley; Deanna M. Clement; Karen A. Stockin (Marine Biology, 2020)

Carbon emissions and climate policy support by local governments in California: a qualitative comparative analysis at the county level - Robert Habans; Matthew Thomas Clement; Andrew Pattison (Journal of Environmental Studies and Sciences, 2019)

Integrated Observations of Global Surface Winds, Currents, and Waves: Requirements and Challenges for the Next Decade - Ana B. Villas Bôas; Fabrice Ardhuin; Alex Ayet; Mark A. Bourassa; Peter Brandt; Betrand Chapron; Bruce D. Cornuelle; J. T. Farrar; Melanie R. Fewings; Baylor Fox-Kemper; Sarah T. Gille; Christine Gommenginger; et al. (Frontiers in Marine Science, 2019)

Forever fissiparous: asexual propagation and stable demography in a tropical and geographically isolated asterinid sea star - Matthew Clements; Kennedy Wolfe; Kit Schwartz; Maria Byrne (Marine Biology, 2019)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Estimating indices of range shifts in birds using dynamic models when detection is imperfect - Matthew J. Clement; James E. Hines; James D. Nichols; Keith L. Pardieck; David J. Ziolkowski (Global Change Biology, 2016)
There is intense interest in basic and applied ecology about the effect of global change on current and future species distributions. Projections based on widely used static modeling methods implicitly assume that species are in equilibrium with the environment and that detection during surveys is perfect. We used multiseason correlated detection occupancy models, which avoid these assumptions, to relate climate data to distributional shifts of Louisiana Waterthrush in the North American Breeding Bird Survey ( BBS ) data. We summarized these shifts with indices of range size and position and compared them to the same indices obtained using more basic modeling approaches. Detection rates during point counts in BBS surveys were low, and models that ignored imperfect detection severely underestimated the proportion of area occupied and slightly overestimated mean latitude. Static models indicated Louisiana Waterthrush distribution was most closely associated with moderate temperatures, while dynamic occupancy models indicated that initial occupancy was associated with diurnal temperature ranges and colonization of sites was associated with moderate precipitation. Overall, the proportion of area occupied and mean latitude changed little during the 1997–2013 study period. Near‐term forecasts of species distribution generated by dynamic models were more similar to subsequently observed distributions than forecasts from static models. Occupancy models incorporating a finite mixture model on detection – a new extension to correlated detection occupancy models – were better supported and may reduce bias associated with detection heterogeneity. We argue that replacing phenomenological static models with more mechanistic dynamic models can improve projections of future species distributions. In turn, better projections can improve biodiversity forecasts, management decisions, and understanding of global change biology.

Cytotoxic oplopane sesquiterpenoids from Arnoglossum atriplicifolium - Jason A. Clement; Rachel M. Bleich; Hailey E. Campbell; Kristin Naylor; Matthew J. Flood; Ryan M. Kelly; Shi-Biao Wu; Edward J. Kennelly; Jeffrey D. Schmitt (Natural Product Research, 2016)

Statistical trend and change-point analysis of land-cover-change patterns in East Africa - Dong-Yun Kim; Valerie Thomas; Jenny Olson; Matthew Williams; Nicolle Clements (International Journal of Remote Sensing, 2013)

Tree structure and cavity microclimate: implications for bats and birds - Matthew J. Clement; Steven B. Castleberry (International Journal of Biometeorology, 2013)

Unincorporated iron pool is linked to oxidative stress and iron levels in Caenorhabditis elegans - Natalie A. Rangel; Lawrence Lin; Kanyasiri Rakariyatham; Albert Bach; Kim Trinh; Matthew H. S. Clement; Chandra Srinivasan (BioMetals, 2012)

Acute and Chronic Effects of Sodium Tungstate on an Aquatic Invertebrate (Daphnia magna), Green Alga (Pseudokirchneriella subcapitata), and Zebrafish (Danio rerio) - Leslie N. Clements; Ranulfo Lemus; Alicia D. Butler; Kate Heim; Matthew R. Rebstock; Carmen Venezia; Michael Pardus (Archives of Environmental Contamination and Toxicology, 2012)